Penerapan Media Canva dalam Pelajaran Bahasa Indonesia Materi Teks Biografi - Dwi Jeliati; Agus Wismanto (Departement of Mathematics Education, 2024)
This study explains the use of Canva media in Indonesian language lessons on biographical texts. The aim of this study is to describe the use of Canva learning media and the response of students to Canva media. The data collection technique used by the researcher is observation with questionnaire collection. This is a qualitative study. Canva is an interactive media that can be utilized by educators in presenting materials. Not only educators, but students can also use this interactive media.